Factors Affecting Transfer Of Training - Ali Abujazar, Samer Saleh (2004)
Training today is a crucial part of an organization's activities. The global and the domestic market are becoming more competitive. To survive and keep their existing on the market, companies should acquire competitive advantages. Skilled employees and workers is one of the most important advantages that companies can take over their competitors. Training is on of the ways that companies follow to improve their employees' skills. Training is costly, and generally speaking, training programs does not achieve theirs goals, due to many problems and barriers. The present study looks at the effect of supervisors support and co-workers support on transfer of training, and the moderating effects of educational background, working experience, and duration of training on the relationship between supervisors support and co-workers support and transfer of training.